2001
DOI: 10.1098/rspa.2000.0702
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study of the focusing of transient and directionally spread surface water waves

Abstract: This paper describes a new laboratory study in which a large number of waves, of varying frequency and propagating in different directions, were focused at one point in space and time to produce a large transient wave group. A focusing event of this type is believed to be representative of the evolution of an extreme ocean wave in deep water. Measurements of the water-surface elevation and the underlying waterparticle kinematics are compared with both a linear solution and a second-order solution based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
104
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 32 publications
(29 reference statements)
13
104
0
Order By: Relevance
“…Consistently, the down-shift becomes less pronounced for increasing degrees of directional spreading, as the effects of spreading serve to decrease the overall degree of nonlinearity (see also Johannessen & Swan 2001). There are no significant trends in the estimated bandwidth k .…”
Section: Spreading Tests (Category A)supporting
confidence: 47%
See 1 more Smart Citation
“…Consistently, the down-shift becomes less pronounced for increasing degrees of directional spreading, as the effects of spreading serve to decrease the overall degree of nonlinearity (see also Johannessen & Swan 2001). There are no significant trends in the estimated bandwidth k .…”
Section: Spreading Tests (Category A)supporting
confidence: 47%
“…Recently, Herbers & Janssen (2016) have shown that the set-down associated with (unidirectional) groups can appear as a significant set-up in Lagrangian buoy records, emphasizing the need to carefully distinguish between Lagrangian and Eulerian field observations. Experimentally, Johannessen & Swan (2001) examined the evolution and focusing of moderately directionally spread focused wave groups and found that the directionality of the wave groups serves to reduce the overall nonlinearity of the waves, affecting the onset of breaking and nonlinear modification of the free waves. Onorato et al (2009) and Toffoli et al (2010) performed experiments and numerical analysis of irregular crossing waves, observing a direct relationship between crossing angle and kurtosis, an indicator of the probability of freak wave occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear wave-wave interactions associated with the evolution of the largest or most extreme wave events (Baldock et al (1996), Johannessen & Swan (2001), (2003)). …”
Section: Introductionmentioning
confidence: 99%
“…A symmetrybased method for separation of harmonics from the calculated free surface time series is used to identify the second-order error waves (for examples of the application of this method see e.g. Baldock et al (1996), Jonathan and Taylor (1997), Johannessen and Swan (2001), Hunt et al (2004) and Borthwick et al (2006b)). The effectiveness of second-order paddle signals in eliminating the contaminating error waves is also examined.…”
Section: Newwave Propagation On a Flat Bedmentioning
confidence: 99%
“…Pioneering laboratory experiments on focused wave groups have been carried out in water of uniform depth (Rapp and Melville (1990), Baldock et al (1996) and Johannessen and Swan (2001)), demonstrating that ocean waves are dispersive and can evolve into transient, localised but energetic groups that focus in shallow coastal waters (Baldock (2006)). It is also plausible that similar focused-wave analysis could be useful in assessing storm-induced wave run-up maxima at beaches and overtopping volumes at coastal defences.…”
Section: Introductionmentioning
confidence: 99%